THE INFLUENCE OF FACILITIES AND SERVICE QUALITY ON CUSTOMER SATISFACTION (CASE STUDY AT VASAKA THE REIZ CONDO APARTMENT) MEDAN - Nurul Sari; Zuhri Zuhri (Jurnal Ekonomi, 2023)
This research discusses customer satisfaction. It's based on short interviews conducted with visitors to Vasaka The Reiz Condo. This research shows an indication of visitor dissatisfaction with the facilities and quality of services provided. The problem is based on short interview observations aimed at visitors. There is visitor dissatisfaction with the facilities and quality of services provided. The long distance to the shopping center and the non-implementation of smart home system innovations are indicated as deficiencies. This study focuses on knowing whether there is an influence between facilities (X1) and service quality (X2) on customer satisfaction (Y). This study used a quantitative descriptive method with multiple linear regression models as the data analysis model. Questionnaires were distributed to 49 visitors who were then processed using the SPSS program. Testing the hypothesis in this study using the R2 test, t-test, and f-test. The results of this study indicate that there is a simultaneous influence between facilities and service quality on customer satisfaction. Based on the partial test, it was also found that there was a positive effect between facilities and customer satisfaction, but on service quality, there was no effect on customer satisfaction as indicated by the resulting negative count. Moreover, the magnitude of the influence between facilities and service quality on customer satisfaction is 33%.